Characterization and Applications of Silver Sulphide Based Membrane Electrodes - Rajbhandari, A; Yadav, AP; Manandhar, K; Pradhananga, RR (Scientific World, 2010)
The polycrystalline materials obtained by co-precipitation of silver sulphide and appropriate silver halide are used to prepare silver sulphide based membrane electrodes selective to the silver, chloride, bromide, iodide, and sulphide ions. The powder materials are characterized by x-ray diffraction, SEM equipped with EDAX. These membrane electrodes are found to give Nernstian response with the appropriate ions in the concentration range from 1x10-1 to 1x10-5 M. The performance of these home made electrodes is at par with the commercial electrodes. The electrodes have been successfully used for the quantitative determination of chloride, bromide iodide, silver, and sulphide ions and also for the determination of thiamine in pharmaceutical preparations. For developing countries like Nepal, who can not afford to procure high cost commercial ion selective electrodes, these home made ion selective electrodes are especially appealing since the electrode can be fabricated with ease in low cost and the electrode is well behaved and sufficiently accurate for the analysis with ion selective electrodes. Key words: Ion selective electrode; Home made ion selective electrode; Silver sulphide; Thiamine; Vitamin B1. DOI: 10.3126/sw.v7i7.3818 Scientific World Vol.7(7) 2009 pp.19-23